RANCANG BANGUN MESIN PENEPUNG UMBI KELADI BENENG DENGAN SISTEM MONO DISK - Aqila Zanjabila; Doni; Dyas Ryfkiansyah; Robert Napitupulu; Yang Fitri Arriyani (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The process of flouring the tubers of taro beneng by Mr. Arizal is still done manually. The dried tubers are pounded using a pestle, then after the results are smooth, filtered using a special filter and if the results are still rough, the mashing process is carried out again. This flouring process takes time and is repeated for a relatively long time. This study aims to design and build a flour milling machine that can produce flour with a mesh fineness level of 0.5 mm and a machine capable of producing flour with a capacity of 10kg/hour. The research method used is the VDI 2222 method, starting with the stages of planning, conceptualizing, designing and completing. Furthermore, the process of making and assembling machines at the Polman Negeri Babel workshop was carried out. Then testing and analysis were carried out to determine the extent to which the results of the design and manufacture of the machine were carried out. Based on the design results, the driving motor uses an electric motor 1 HP 1400 RPM with a shaft diameter of 35mm. The transmission system uses a pulley and belt, the penepung system uses a mono disk system. Based on the test results, the average machine is able to flour beneng taro tubers with a capacity of 11.2 kg/hour with 0.5mm mesh fineness.